Microfluidics applications for high-throughput single cell sequencing - Wen-min Zhou; Yan-yan Yan; Qiao-ru Guo; Hong Ji; Hui Wang; Tian-tian Xu; Bolat Makabel; Christian Pilarsky; Gen He; Xi-yong Yu; Jian-ye Zhang (Journal of Nanobiotechnology, 2021)
Abstract The inherent heterogeneity of individual cells in cell populations plays significant roles in disease development and progression, which is critical for disease diagnosis and treatment. Substantial evidences show that the majority of traditional gene profiling methods mask the difference of individual cells. Single cell sequencing can provide data to characterize the inherent heterogeneity of individual cells, and reveal complex and rare cell populations. Different microfluidic technologies have emerged for single cell researches and become the frontiers and hot topics over the past decade. In this review article, we introduce the processes of single cell sequencing, and review the principles of microfluidics for single cell analysis. Also, we discuss the common high-throughput single cell sequencing technologies along with their advantages and disadvantages. Lastly, microfluidics applications in single cell sequencing technology for the diagnosis of cancers and immune system diseases are briefly illustrated.